Biomaterials and regenerative medicine - Ma, Peter X. (Cambridge University Press;, 2014)
"Written by world-leading experts, this book focusses on the role of biomaterials in stem cell research and regenerative medicine. Emphasising basic principles and methodology, it covers stem cell interactions, fabrication technologies, design principles, physical characterisation and biological evaluation, across a broad variety of systems and biomaterials. Topics include: stem cell biology, including embryonic stem cells, IPS, HSC and progenitor cells; modern scaffold structures, including biopolymer, bioceramic, micro- and nanofiber, ECM and biohydrogel; advanced fabrication technologies, including computer-aided tissue engineering and organ printing; cutting-edge drug delivery systems and gene therapy techniques; medical applications spanning hard and soft tissues, the cardiovascular system and organ regeneration. With a contribution by Nobel laureate Shinya Yamanaka, this is a must-have reference for anyone in the field of biomaterials, stem cell biology and engineering, tissue engineering and regenerative medicine"--